Clearing up Vietnamosasa (Poaceae, Bambusoideae): typification and nomenclature of a distinctive paleotropical bamboo genus - Haevermans, Thomas; Nguyen, Bich Loan; Gurgand, Jacques; Haevermans, Agathe; Dransfield, Soejatmi; Diep, My Hanh (Phytotaxa, 2013)
This paper aims to clarify and stabilize the nomenclature of the singular fire-adapted South-East Asian bamboo genus Vietnamosasa Nguyen (1990: 221), and the specific taxa it comprises, by designating lectotypes and neotypes to allow accurate application of the published names. Little attention has been given to this genus in the last 10 years, partly because its three published species are difficult to distinguish from each other, but mostly due to the fact that the type specimen of the type species is reportedly lost, and the fact that the original description is inadequate and does not include illustrations of the new taxa. The genus is readily recognizable by its special “grass-mound” appearance and the morphology of its subterranean organs: rhizomes as well as subterranean vegetative axes growing horizontally, which allow the bamboo to thrive in fire prone areas (Dransfield 2000).